Non-anomalous generalized chiral Schwinger model - Dutra, Alvaro de Souza [UNESP] (World Scientific Publishing, 1997)
Recently, Basseto and Griguolo1 did a perturbative quantization of what they called a generalized chiral Schwinger model. As a consequence of the kind of quantization adopted, some gauge-dependent masses raised in the model. On the other hand, we discussed the possibility of introducing a generalized Wess-Zumino term,2 where such gauge-dependent masses did appear. Here we intend to show that one can construct a non-anomalous version of a model which include that, presented by Basseto and Griguolo as a particular case, by adding to it a generalized Wess-Zumino term, as proposed in Ref. 2. So we conclude that it is possible to construct a gauge-invariant extension of the model quoted in Ref. 1, and this can be done through a Wess-Zumino term of the type proposed in Ref. 2.